SOSIALISASI MOBILE LEARNING UNTUK MENINGKATKAN SISTEM PEMBELAJARAN PADA MASYARAKAT DESA BANGUNKERTO KECAMATAN TURI KABUPATEN SLEMAN - Gatot Santoso; Slamet Hani (Universitas Sahid Surakarta, 2016)
A university is present in the community to assume the function of Tri Dharma Perguruan Tinggi, which is the function of Education and Teaching, Research, and Community Service. In order for Universities to be in direct contact with the community through the practice of science and technology, then the activities of community servicemust be done. Program of Community Service (Abdimas) is not only done by lecturers, but also students who are concrete tangible Real Work Lecture (KKN).KKN program at the Institute of Science & Technology AKPRIND Yogyakarta, as well as efforts to improve empathy and awareness of students in the community andapply science, especially science and technology in the midst of society. The process of implementing this KKN also get guidance from lecturers. In the guidance of this KKN,lecturers also play a role in the implementation of community service. With the involvement of this lecturer is expected to implement KKN can run in accordance withthe policy of the Institute. As the implementation of community service, especially at the location of KKN Wukirsari Bantul District, KKN team and lecturers provide science and technologythemed training. The training provided includes a mobile leaning targeted at the community.